2003
DOI: 10.1021/es034257j
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PCB Monitoring Using Time-of-Flight Mass Spectrometry with Picosecond Laser Ionization

Abstract: The study demonstrates the applicability of laser ionization time-of-flight mass spectrometry for real-time measurement of polychlorinated biphenyls (PCBs). Picosecond 266-nm laser light ionization reduced fragmentation and provided very high PCB detection sensitivity. This high sensitivity has advantages in terms of real-time monitoring capability as compared to the conventional GC-ECD or GC-MS methods, which require at least several days for the analysis of PCBs. Detection sensitivity of under 0.01 mg/Nm3 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 16 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…10,38 In the future, the long-term reliability of the monitoring system will be verified, and practical applications will be pursued as innovative tools for safety management in various types of PCB treatment plants. ANALYTICAL SCIENCES JANUARY 2004, VOL.…”
Section: Resultsmentioning
confidence: 99%
“…10,38 In the future, the long-term reliability of the monitoring system will be verified, and practical applications will be pursued as innovative tools for safety management in various types of PCB treatment plants. ANALYTICAL SCIENCES JANUARY 2004, VOL.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that a laser emitting at this wavelength was more effective for ionizing PCBs than a laser emitting at 280, 300, or 320 nm. 78,79 By taking into account the general concentration of PCDD/Fs in a flue gas, these compounds can be detected once per hour using this "quasireal-time monitoring system" without any pretreatment, including the elution time required for a GC run.…”
Section: Discussionmentioning
confidence: 99%
“…43) New findings presented here include the e$cient trapping of laser-ionized PCB ions using the dynamic trapping time-of-flight mass spectrometry (TOFMS), as well as the simulation of electric field control conditions for e$cient trapping, and observation of the e#ectiveness of reducing the speed of the ions introduced into the trap apparatus. 41), 42) Evaluations of accuracy based on comparisons with the results of the conventional method (gas sampling/gas chromatography mass spectrometry; gas sampling/ GC-MS) demonstrated a coe$cient of variation of ῌ30῍.…”
Section: )῏68)mentioning
confidence: 99%